Water infiltration under different land use in miombo woodlands outside Morogoro, Tanzania - Nord, Helena (SLU/Dept. of Forest Ecology and Management, 2008)
Infiltration capacity is a measure of how much water that can enter the soil and hence become available to plant roots and micro organisms. A high infiltration capacity also means that less water is available for runoff and subsequent erosion. Infiltration capacity, bulk density and soil organic carbon content were measured in six land use types in miombo woodlands; natural forest, degraded forest, intensive agriculture, abandoned agriculture, degraded regenerating forest and Albizia plantation. The measurements were carried out in miombo woodlands about 50 km west of Morogoro, Tanzania. In the intensive agriculture and the abandoned agriculture the higher infiltration capacity was created by the mechanical disturbance and in the abandoned agricultural case also by the subsequent dense grass vegetation. The mechanical disturbance is, together with the presence of the tree roots, probably the cause of the high infiltration capacity in the Albizia plantation. Since the infiltration capacity increased after the establishment of an Albizia plantation, as well as the ability of the soil to receive high intensity rain increased when a degraded forest was left to regenerate and an Albizia plantation was established, this suggests that improved vegetation on a previously degraded land is positive. The mechanical disturbance created a low bulk density in the intensive agriculture and the abandoned agriculture; the dense grass may also have caused the bulk density in the abandoned agriculture to be the lowest of all land uses. Since a large number of measurements have been performed in this study it is also possible to estimate the variation within the land uses. The analysis showed that the variation within the intensive agriculture was significantly higher than in the natural forest, which may be a result of the mechanical disturbance in the intensive agriculture and a small variation in the natural forest.